Missed Tillaux Fracture and Syndesmosis Injury in Adult: Arthroscopic Assisted Reduction and Fixation - Nuno Oliveira; Pedro Pinho; Mário Baptista; Daniel Freitas; Pedro Varanda; Bruno S. Pereira (Revista Brasileira de Ortopedia, 2021)
Abstract Tillaux fractures are fractures of the lateral margin of the distal tibia, usually reported in children between 12 and 14 years old. As intraarticular fractures, they require anatomic reduction and fixation to avoid posttraumatic complications. Since the injury mechanism is external rotation of the foot on the leg, these injuries are commonly associated with other fractures or ligamentous lesions. Currently, arthroscopy is being increasingly used to assist and improve surgical treatment of ankle fractures. The authors describe a 12-month follow-up of a rare case of a missed Tillaux fracture associated with syndesmosis injury in a 76-year-old polytrauma patient, successfully treated by arthroscopically-assisted reduction and internal fixation.